Scaling up the delivery of refractive error services within a district health system: the KwaZulu-Natal, South Africa experience - Naidoo, Kovin S (BioMed Central, 2013)
BACKGROUND: In South Africa, the health service is based on a Primary Health Care (PHC) philosophy with the District Health System (DHS) as the locus of delivery. However eye care services, particularly primary eye care, refractive error and low vision, have not been prioritised accordingly. Hence the aim of the Giving Sight to KwaZulu-Natal (GSKZN) project was to integrate the delivery of eye care services into the district health system, with emphasis on addressing the need for uncorrected refractive error and low vision services. The project was implemented in the KwaZulu-Natal province, South Africa, to scale up the delivery of refractive error services utilising a four pronged approach; including advocacy, human resource development, equipment provision and research. METHODS: This paper is a description of the project and a retrospective analysis of data received through the course of the project from July 2007 to June 2011. Data were collected from training registers, equipment schedules and service delivery reports from institutions. Reports from the data base were then analysed and achievements in training and trends in service delivery were determined. RESULTS: Over a four year period (July 2007 and July 2011) 1004 persons received training in rendering eye health services appropriate to their level of deployment within the DHS. During the course of the project, these 1004 persons examined 1 064 087 patients. Furthermore, the total number of clinics offering primary eye care, refractive error and low vision services increased from 96 (10%) to 748 (76%). With increased numbers of PHC Nurses trained in primary eye care, a subsequent decrease of 51.08 percent was also observed in the number of patients seeking services at higher levels of care, thus streamlining eye health service delivery. CONCLUSION: This project has shown that scaling up can occur in delivering eye health services within a health district, through a multi-faceted approach that encompasses focused training, advocacy, development of appropriate infrastructure and the development of referral criteria with clear guidelines for the management of patients.